Dexmedetomidine inhibits abnormal muscle hypertrophy of myofascial trigger points via TNF-α/ NF-κB signaling pathway in rats - Liu, Mingjian; Liu, Yu; Li, Xuan; Pei, Miao; Han, Mei; Qi, Feng (Frontiers in Pharmacology, 2022)
Myofascial pain syndrome (MPS) is a chronic pain disorder with inflammation-related primarily characterized by the presence of myofascial trigger points (MTrPs). Myocyte enhancer factor 2C (MEF2C) is involved in the occurrence of a variety of skeletal muscle diseases. However, it is not yet clear if MEF2C is involved in MTrPs. The purpose of this study was to investigate whether MEF2C was involved in the inflammatory pathogenesis of MTrPs. In the present study, we used RNA sequencing (RNA-seq) to compare the differential expression of myocyte enhancer factor 2C (MEF2C) in healthy participants and MTrPs participants. the widely used rat MTrPs model was established to research the upstream and downstream regulatory mechanism of MEF2C and found that MEF2C was significantly increased in patients with MTrPs. Dexmedetomidine (Dex) was injected intramuscularly in the MTrPs animal to assess its effects on MEF2C. The expression of MEF2C protein and mRNA in skeletal muscle of rats in the MTrPs group were up-regulated. In addition, the expression of TNF- α, p-P65, MLCK, and Myocilin (MyoC) was up-regulated and the mechanical pain threshold was decreased. Peripheral TNF- α injection significantly decreased the mechanical pain threshold and increased the expression of p-P65, MLCK, MEF2C, and MyoC in healthy rats. Maslinic acid increased the mechanical pain threshold and inhibited the expression of p-P65, MLCK, MEF2C, and MyoC. In addition, peripheral injection of DEX in MTrPs rats also inhibited the expression of TNF- α, p-P65, MLCK, MEF2C, and MyoC. These results suggest that MEF2C is involved in the inflammatory pathogenesis of MTrPs and DEX serves as a potential therapeutic strategy for the treatment of MPS.